In vivo functions of miRNAs in mammalian spermatogenesis - Chen, Jian; Han, Chunsheng (Frontiers in Cell and Developmental Biology, 2023)
MicroRNAs (miRNAs) are believed to play important roles in mammalian spermatogenesis mainly because spermatogenesis is more or less disrupted when genes encoding key enzymes for miRNA biogenesis are mutated. However, it is challenging to study the functions of individual miRNAs due to their family-wise high sequence similarities and the clustered genomic distributions of their genes, both of which expose difficulties in using genetic methods. Accumulating evidence shows that a number of miRNAs indeed play important roles in mammalian spermatogenesis and the underlying mechanisms start to be understood. In this mini review, we focus on highlighting the roles of miRNAs in mammalian spermatogenesis elucidated mainly by using in vivo genetic methods and on discussing the underlying mechanisms. We propose that studies on the roles of miRNAs in spermatogenesis should and can be conducted in a more fruitful way given the progress in traditional methods and the birth of new technologies.